The Prevalence of Acute Kidney Injury in Neonates with Asphyxia - Saboute, Maryam; Parvini, Behnaz; Khalessi, Nasrin; Kalbassi, Zohreh; Kalani, Majid; khosravi, Nastran (Journal of Pediatric Nephrology, 2016)
Introduction: Asphyxia is a common cause of mortality and morbidity among neonates. Following severe asphyxia and ischemia, reperfusion occurs which damages vital organs like the kidneys. This study was conducted to determine the prevalence of AKI based on the definition of a serum creatinine level higher than 1.5 mg/dL, in neonates with asphyxia. Materials and Methods: This retrospective study was performed in Ali-Asghar and Shahid-Akbar-Abadi Hospitals, Tehran, Iran in a period of one year. The medical documents of all newborns diagnosed with asphyxia were studied. The asphyxia grade was determined according to the asphyxia Sarnat criteria. The kidney function was evaluated based on the serum creatinine level. Results: Thirty-eight cases met the inclusion criteria. There were 13 Sarnat grade-1 cases (34.2%), 19 grade 2 cases (50%), and 6 grade 3 patients (17.6%). Three (7.8%) patients (2 patients in grade 3 and one patient in grade 2 of the Sarnat grading scale) developed AKI. AKI was detected in 33% of the patients in grade 3 and 5.2% of the patients in grade 2 of the Sarnat grading scale. Nine patients (23%) died, of whom 83% were in grade 3 and 16.9% in grade 2 of asphyxia. Conclusions: AKI developed in 7.8% of the cases, of whom 33% were in grade 3 and 5.2% were in grade 2 of the Sarnat grading scale. The low rate of AKI development in our study might be duo to the small sample size and patient mortality in the first 3 days of life. Keywords: Acute kidney injury; Neonates; Asphyxia.